Physio-biochemical and morphological characters of halophyte legume shrub, Acacia ampliceps seedlings in response to salt stress under greenhouse - Theerawitaya, Cattarin; Tisarum, Rujira; Samphumphuang, Thapanee; Singh, Harminder P.; Suriyan Cha-Um,; Kirdmanee, Chalermpol; Takabe, Teruhiro (Frontiers in Plant Science, 2015)
Acacia ampliceps (salt wattle), a leguminous shrub, has been introduced in salt-affected areas in the northeast of Thailand for the remediation of saline soils. However, the defense mechanisms underlying salt tolerance A. ampliceps are unknown. We investigated various physio-biochemical and morphological attributes of A. ampliceps in response to varying levels of salt treatment (200–600 mM NaCl). Seedlings of A. ampliceps (25 ± 2 cm in plant height) raised from seeds were treated with 200 mM (mild stress), 400 and 600 mM (extreme stress) of salt treatment (NaCl) under greenhouse conditions. Na+ and Ca2+ contents in the leaf tissues increased significantly under salt treatment, whereas K+ content declined in salt-stressed plants. Free proline and soluble sugar contents in plants grown under extreme salt stress (600 mM NaCl) for 9 days significantly increased by 28.7 (53.33 μmol g–1 FW) and 3.2 (42.11 mg g–1 DW) folds, respectively over the control, thereby playing a major role as osmotic adjustment. Na+ enrichment in the phyllode tissues of salt-stressed seedlings positively related to total chlorophyll (TC) degradation (R2 = 0.72). Photosynthetic pigments and chlorophyll fluorescence in salt-stressed plants increased under mild salt stress (200 mM NaCl). However, these declined under high levels of salinity (400–600 mM NaCl), consequently resulting in a reduced net photosynthetic rate (R2 = 0.81) and plant dry weight (R2 = 0.91). The study concludes that A. ampliceps has an osmotic adjustment and Na+ compartmentation as effective salt defense mechanisms, and thus it could be an excellent species to grow in salt-affected soils.